DNA Methylation Inhibits the Expression of CFSH in Mud Crab - Jiang, Qingling; Lin, Dongdong; Huang, Huiyang; Wang, Guizhong; Ye, Haihui (Frontiers in Endocrinology, 2020)
Crustacean female sex hormone (CFSH) is a key regulator of crustacean sex differentiation. The expression of Sp-CFSH in the mud crab Scylla paramamosain showed a tissue-specific and gender-variant pattern. To explore the role of DNA methylation in Sp-CFSH expression, the 5’-flanking region of Sp-CFSH was cloned, and one CpG island containing 12 CpG sites was found. Results of sodium bisulfite sequencing and methylated DNA immunoprecipitation showed that CpG island methylation was stable in the eyestalk ganglion during ovarian development of the females, which was significantly lower than that in the muscle of the females and in the eyestalk ganglion of the males. Such results suggested that the involvement of DNA methylation in regulating Sp-CFSH expression followed an eyestalk ganglion-specific and gender-variant pattern. The analysis of CpG dinucleotides sites methylation and activity of the site-directed mutation (SDM) reporter vector further demonstrated that methylation inhibited Sp-CFSH expression by blocking the binding of transcription factor Sp1. The finding suggested for the first time the involvement of CpG methylation in the regulation of Sp-CFSH expression.